Design and Analysis of Backplane Mechanism for New Nursing Bed Chair - Zhongren Zhou; Chengtao Yu; Xiangyu Zhou; Xuebin Sun (Jixie chuandong)
Aiming at the problem that the back module of the existing nursing bed chair is difficult to realize the mutual change between the postures of the nursing bed and wheelchair，a new type of back plate mechanism is proposed. A serial backplane spatial combination mechanism is formed by connecting multiple mechanisms with single function，and its spatial freedom is analyzed to meet the motion demand. The target size is parameterized，and the optimal position of the support connecting rod，backplane and support frame hinge is obtained using the minimum inclusive area method. According to the geometric relationship and statics analysis result of the backplane mechanism，the JC35D electric push rod with rated stroke and working stroke of 175 mm and 230 mm and self-locking force of 1 000 N is used as the driving mechanism. The backplane mechanism of the nursing bed chair is designed according to the optimized parameters and the drive device type，and the overall virtual prototype is assembled by SolidWorks. The simulation finite element analysis plug-in is used to analyze the stress of the backplane under the posture of the nursing bed chair，and the safety and reliability of the structural strength are verified. Under the posture of nursing bed，Adams View software is used to carry out the static rollover simulation test of the mechanism，and the stability requirement of the backplane under the rollover test load is verified.